2020
DOI: 10.3390/ma13194314
|View full text |Cite
|
Sign up to set email alerts
|

Additive Effect of Platelet Rich Fibrin with Coronally Advanced Flap Procedure in Root Coverage of Miller’s Class I and II Recession Defects—A PRISMA Compliant Systematic Review and Meta-Analysis

Abstract: Aim: This systematic review and meta-analysis aims to assess the additive effect of leukocyte and platelet-rich fibrin (L-PRF) on coronally advanced flap (CAF) procedures in root coverage of Miller’s class I and II gingival recession defects. Review methodology: A comprehensive search in MEDLINE (PubMed), Scopus and CENTRAL (the Cochrane Central Register of Controlled Trials), along with an additional hand search, provided eight randomized clinical trials to be included in this review. A total of 167 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 49 publications
3
15
0
1
Order By: Relevance
“…In the quantitative analysis of the effect of PRF on periodontal surgery, the heterogeneity among the studies was as high as the meta-analysis of Castro et al [17], Tarallo et al [39], Panda et al [42], Li et al [38], and Li et al [41]. Heterogeneity may come from different clinical research methodology and implementation processes.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…In the quantitative analysis of the effect of PRF on periodontal surgery, the heterogeneity among the studies was as high as the meta-analysis of Castro et al [17], Tarallo et al [39], Panda et al [42], Li et al [38], and Li et al [41]. Heterogeneity may come from different clinical research methodology and implementation processes.…”
Section: 2mentioning
confidence: 99%
“…In terms of gingival recession, Moraschini and Barboza Edos [40] have reported in 2016 that the use of PRF membranes did not improve the root coverage, keratinized mucosa width, or CAL of Miller classes I and II gingival recessions compared with the other treatment modalities. On the contrary, the meta-analysis of Li et al [41] and Panda et al [42] suggested that PRF when used in addition to coronally advanced flap (CAF) showed favorable results for the treatment of gingival recession defects. Moreover, He et al [43] reported that local application of PRF after lower third molar extraction was a valid method for relieving pain and 3-day postoperative swelling and reducing the incidence of alveolar osteitis.…”
mentioning
confidence: 99%
“…The latest systematic review according to Panda et al 2020 analyzed only the effect of L-PRF to CAF and not also between L-PRF and CTG which is the standard in root coverage procedures. Moreover, in the meta-analyses, the inclusion of Dixit et al 2018 [ 46 ] in the multiple recession group might affect the results for its design as a study for single and not multiple recessions [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this case study, the use of PRF probably had the potential to preserve pulp viability in the adjacent tooth 24. Platelet-rich preparations can be also used for soft tissue augmentation as an alternative to connective tissue graft (CTG), usually in combination with a coronally advanced flap [34]. However, in the presented case, gingival augmentation was only partial.…”
Section: Discussionmentioning
confidence: 94%